Penggunaan Strategi Pembelajaran Kooperatif Melalui Eksperimen Dalam Pembelajaran Komposisi dan Dekomposisi Bilangan Bagi Anak Slow Leaner - U.Usep; Imelda Susila Wirahardja; Winda Safarin; Sri Rahmawat; Budi Susetyo (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the results of cooperative learning strategies through experiments in learning to count for slow learner children. We combined quantitative and qualitative methods in analyzing the data collected during the research. The profile of a Slow Learner student concluded through assessments is used as the basis for creating a Learning Program Plan that uses cooperative learning strategies through experimentation. The research results show that cooperative learning increases the motivation and active learning of regular and special students while improving the learning outcomes of children with special needs, and all students in general. This can be seen from the scores obtained by both groups which were above average and the attitudes shown in learning. We hope that the results of this research can provide information about creative ways of cooperative mathematics learning for Slow Learner students in an inclusive context.